SOCIAL PHENOMENON IN POETRY MONEY MESSAGE AND SHAVE BEFORE SLEEP BY JOKO PINURBO - Irsyad Zulfahmi (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2014)
The objective of the reserch is to identify the picture of social conditions contained in two poems by Joko Pinurbo, namely the Money Message and Shave Before Sleeping.Based on the results of research conducted, it can be concluded; in form, the poem Messages Money consists of four temple and fifteen rows, depicting how someone who tried to improve the conditions of life by